Arabic language textbook for the sixth literary grade In Iraqi schools / a critical study (Journal of the College of Basic Education, 2025)
This study is concerned with critically analyzing the book (Arabic Language) for the sixth literary grade. It is part of the efforts that attempt to monitor, criticize and evaluate the Arabic language curriculum. To reach the level that meets the ambition, and to achieve the educational goals for which these books were written, and the researcher had detailed references in various aspects of the book linguistically, methodologically, scientifically, and technically, and accordingly the researcher concluded that the book needs to be reviewed, corrected, and revised,agree wite.